Adaptive Re-Use Potentials of Post Office Buildings as Examples of British Colonial Heritage in Nigeria and North Cyprus - Kolo, Dan Ndataidi (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2015)
ABSTRACT: Adaptive Reuse is known to be one of the techniques used in conservation of historic buildings. Adaptive Reuse of historic buildings becomes more important as society develops. Architectural heritage refers to buildings which are inherited from past generations. There are tendencies that older historic buildings would be abandoned and deemed inappropriate to be used, this however leads to the demolition, construction of new buildings or adapting the old buildings to new functions. This makes it necessary for the British Colonial buildings to be conserved. The interior components within these buildings should be preserved within the new use. British Colonial buildings in Nigeria and North Cyprus are edifice from the past, coming from the Period of Colonial rule in both countries. These buildings hold characters of historic times, 1900-1960 for Nigeria and 1878-1960 for Cyprus with historic architectural styles, therefore sustaining and reusing them for new purposes is advisable in other to retain history. Thesis covers the historical background to Adaptive Reuse, from the inception of preservation of historic buildings. The main purpose of preserving these heritage buildings is to help prolong their architectural, historic and aesthetic characters. Beside of these, it is mentioned the importance of this heritage building, their potentials, the best way to conserve and Adaptive Reuse potentials of these periods building. The first chapter contains a general introduction about the thesis; chapter two includes theoretical background of historic building conservation; chapter three includes British Colonial Period in the World and selected countries; chapter four features case study analysis; chapter five includes case study findings and discussions. And chapter six includes conclusions and recommendations. Last parts of the study, references are given. Keywords: Colonial Buildings, Heritage, Adaptive Re-use, Nigeria, North Cyprus, Indoor Space. ………………………………………………………………………………………………………………………… ÖZ: Tarihi değere sahip binaların korunmasında ve yaşatılmasında bilinen yaklaşımlardan biri de ‘yeniden işlevlendirme’dir. Tarihi binaları işlevlendirerek yeniden kullanabilmek toplum belleği için çok önemlidir. Eski, tarihi binalar işlev eskimesinden dolayı kullanılmıyor ve kullanıma uygusuz olarak varlık gösteriyorlar. Bu durum onların yıkılmaya terk edilmesi ve yeni binalar yapılması sonucunu doğurabilir; bu durumun olmaması için yeniden işlevlendirerek yaşama kazandırılması hiç kuşkusuz en doğru yaklaşımdır. Bu yaklaşım, İngiliz Sömürge dönemi yapıları için de uygulanmalıdır. Bu döneme ait yapıların mimari miras olarak kabul edilip, korunması ve yaşatılması yeniden işlevlendirilerek yapılmalıdır. İngiliz Sömürge dönemi yaşamış Nijerya ve Kıbrıs’ta sömürge dönemi yapıları vardır ve o dönemin tanıklarıdırlar. Mimari miras olarak kabul edilen bu yapılar, 1900 – 1960 yılları arasında Nijerya’da ve 1878 – 1960 yılları arasında Kıbrıs’ın Kuzey’inde sömürge döneminde inşa edilmiş, tarihi, dönemin karakteristik özelliklerini taşıyan, tarzları (stilleri) olan ve bahsedilen her iki ülkeyi de yeniden yapılandırma amacı ile inşa edilmişlerdir. Tarihe tanıklık etmiş bu yapıların korunması gerekir. Bu binaların önemlerini vurgulamak, varlıklarının değerini söylemek, potansiyellerini ortaya koymak, nasıl korunacaklarının altını çizmek çalışmanın temel amacıdır. Bu amaçla, birinci bölüm olan genel giriş bölümünde, çalışmanın neleri içerdiği, sınırları, amacı, yöntemi, strüktürü açıklanmaktadır. İkinci bölüm, tarihi değeri olan söz konusu yapıların altyapısı ve korumaya yönelik teorik bilgiler sunulmaktadır. Üçüncü bölüm, dünyadaki İngiliz Sönürge dönemi ve seçilen ülkelerdeki durum irdelenmektedir. Dördüncü bölüm, vaka çalışması analizleri yapılmaktadır. Beşinci bölüm ise, çalışmanın bulguları ortaya konarak tartışmalar yapılıp altıncı bölümle de çalışma tavsiyeleri de içeren sonuç bölümü ile noktalandırılmıştır. Çalışmanın son bölümünde referanslar verilmiştir. Anahtar Kelimeler: Koloni Dönemi yapıları, miras, yeniden işlevlendirme, Njerya, Kuzey Kıbrıs, İç Mekan.
Master of Science in Interior Architecture. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Architecture, Dept. of Interior Architecture, 2015. Supervisor: Assoc. Prof. Dr. Kağan Günçe.
Keywords: Interior Architecture; Historic buildings - Conservation and restoration - Nigeria; Historic buildings - Conservation and restoration - Cyprus, North; Historic buildings - Remodeling for other use; Colonial Buildings, Heritage, Adaptive Re-use, Nigeria, North Cyprus, Indoor Space